The Effect of Internal Audit and the Effectiveness of Internal Control on the Ability to Detect Fraud - Angelia Christie; Cris Kuntadi (Sean Institute, 2024)
Fraud detection is needed in a management in order to be able to control and prevent failure in achieving goals. This research uses a literature review analysis method with qualitative characteristics, with sources from google scholar, ebooks and other online media. This study aims to examine the effect of internal audit and the effectiveness of internal control on fraud detection capabilities. The results of this study are in the form of internal audit variables and the effectivenss of internal control which have a significant effect on fraud detection capabilities.